Relevance of Ecolabel Scheme on Textile/Textile Product to Support Sustainable Consumption and Production Pattern in Indonesia - Rudyismanto, Reynold; Prasetyo, Teguh; Purwaka, Tommy Hendra (Universitas Pelita Harapan, 2023)
Everyone has the right to have access to sufficient, safe and physically accessible water for personal and domestic use. River is one of the water resources, which is highly necessary for the people who live in close contact with it. In the past few years there have been several law cases of water pollution in some Indonesian rivers caused by textile factories, who had been releasing untreated wastewater into the river. The wastewater had become harmful to humans and river life mostly due to toxic synthetic dyes chemicals used in textile production. This research aims to provide the reasons to apply ecolabel scheme on the textile/textile products in regards to sustainable development especially the Sustainable Development Goal (SDG) number 12: Sustainable Consumption and Production, which requires that people urgently reduce ecological footprint by changing the way they produce and consume goods and resources. This is a qualitative juridical normative study with statute approach, historical approach and philosophical approach, conducted by using secondary data and are collected by using the method of literature review. According to this research, ecolabel scheme on textile/textile product is relevant to support sustainable consumption and production pattern in Indonesia because it is a way to protect and preserve the environment especially river water in accordance with the international environmental laws regarding sustainable development, Indonesian legislation regarding sustainable development, and Dignified Justice (a justice concept based on Pancasila, the Five Principles of Indonesian State).